Polymer fine particle, resin composition, and molding

Polymer fine particles with farnesene units and a graft portion address the issues of fluidity, impact resistance, and transparency in resin compositions, resulting in improved molded articles with reduced plastic usage.

JP2025010903APending Publication Date: 2025-01-23KANEKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023113203
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Existing resin compositions lack excellent fluidity, impact resistance, and transparency, particularly in molded articles made from thermoplastic or thermosetting resins.

Method used

The development of polymer fine particles comprising an elastic body with farnesene units and a graft portion, having a volume average particle diameter of less than 50 nm, which are incorporated into resin compositions to enhance fluidity and impact resistance while maintaining transparency.

Benefits of technology

The polymer fine particles provide resin compositions with improved fluidity and molded articles with enhanced impact resistance and transparency, while also reducing the amount of plastic used, contributing to sustainable production goals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010903000001
    Figure 2025010903000001
  • Figure 2025010903000002
    Figure 2025010903000002
Patent Text Reader

Abstract

To provide polymer fine particles which can provide a resin composition excellent in flowability and a molding excellent in impact resistance.SOLUTION: Polymer fine particles have an elastic body which contains a farnesene unit and has a volume average particle diameter of less than 50 nm, and a graft part which is graft-coupled to the elastic body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polymer microparticles, a resin composition, and a molded article. [Background technology]

[0002] As described in Patent Document 1, a method of adding an elastomer, in particular polymer fine particles, to a thermoplastic resin or a thermosetting resin is widely used to improve the impact resistance of the resin.

[0003] From the viewpoint of processability, polymer microparticles capable of providing resin compositions with excellent flowability are required. Also, molded articles with excellent transparency are sometimes required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 038724 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of one embodiment of the present invention is to provide polymer microparticles which can provide a resin composition having excellent flowability and a molded article having excellent impact resistance and transparency. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems, and have completed the present invention. That is, one embodiment of the present invention includes the following configuration.

[0007] [1] Polymer microparticles comprising an elastomer containing farnesene units and having a volume average particle size of less than 50 nm, and a graft portion grafted to the elastomer.

[0008] [2] The polymer microparticles according to [1], wherein the elastomer contains one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.

[0009] [3] The polymer microparticles according to [1], wherein the elastomer contains 5.0% by weight to 99.9% by weight of the farnesene unit, and contains a total of 0.1% by weight to 95.0% by weight of one or more structural units selected from the group consisting of diene units, vinyl units and polyfunctional units other than the farnesene unit, based on 100% by weight of structural units.

[0010] [4] The polymer microparticles according to [3], wherein the elastomer contains, based on 100% by weight of constituent units, 0% by weight to 95.0% by weight of diene units other than the farnesene units, 0% by weight to 50.0% by weight of the vinyl units, and 0% by weight to 20.0% by weight of the polyfunctional units.

[0011] [5] The polymer microparticles according to any one of [1] to [4], wherein the elastic body contains a styrene unit and / or an alkyl (meth)acrylate unit.

[0012] [6] The polymer microparticles according to any one of [1] to [5], wherein the elastomer contains a styrene unit, and the content of the styrene unit is 20.0% by weight or less in 100% by weight of the constituent units of the elastomer.

[0013] [7] The polymer microparticles according to any one of [1] to [6], wherein the graft portion contains a styrene unit.

[0014] [8] The polymer microparticles according to [7], wherein the elastic body contains a styrene unit.

[0015] [9] The polymer microparticles according to [7], wherein the elastic body does not contain a styrene unit.

[0016]

[10] A resin composition comprising the polymer fine particles according to any one of [1] to [9] and a matrix resin.

[0017]

[11] The resin composition according to

[10] , wherein the matrix resin is polyvinyl chloride.

[0018]

[12] A molded article obtained by molding the resin composition according to

[10] or

[11] . Effect of the Invention

[0019] According to one embodiment of the present invention, there is an effect that it is possible to provide polymer microparticles that can provide a resin composition having excellent flowability and a molded article having excellent impact resistance and transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0021] In this specification, the term "X unit" contained in a polymer, copolymer, or resin means a "structural unit derived from an X monomer." For example, the term "farnesene unit" means a "structural unit derived from a farnesene monomer."

[0022] [1. Polymer microparticles] The polymer microparticles according to one embodiment of the present invention have an elastomer that contains farnesene units and has a volume average particle size of less than 50 nm, and a graft portion that is graft-bonded to the elastomer.

[0023] In this specification, "polymer microparticles according to one embodiment of the present invention" may be referred to as "polymer microparticles of the present invention". Furthermore, "resin composition according to one embodiment of the present invention" may be referred to as "resin composition of the present invention", and "molded body according to one embodiment of the present invention" may be referred to as "molded body of the present invention". "Elastomeric body according to one embodiment of the present invention" may be referred to as "elastic body of the present invention", and "graft portion according to one embodiment of the present invention" may be referred to as "graft portion of the present invention".

[0024] Since the present polymer microparticles have the above-mentioned configuration, they have the advantage of being able to provide polymer microparticles that can provide a resin composition having excellent fluidity and a molded article having excellent impact resistance and transparency.

[0025] In the present specification, the term "a resin composition has excellent fluidity" means that, when the resin composition is subjected to the measurement of the flow rate according to the method B described later in the examples, the result is 10.0 (cm 3 / sec×10 -2 That is, when the present resin composition is subjected to the measurement of the flow rate according to the method B described later in the examples, the result is 10.0 (cm 3 / sec×10 -2 In this specification, the term "cm 3 / sec×10 -2 ) means {(cm 3 / sec)×10 -2} is intended.

[0026] In this specification, the term "a molded article has excellent impact resistance" means that, when the molded article is subjected to impact resistance measurement as described in detail in the Examples below, the result of the IZOD test at 23°C is 32.1 kJ / m 2That is, when the impact resistance of the molded article is measured as described in detail in the Examples below, the result of the IZOD test at 23° C. is 32.1 kJ / m or more. 2 It has the advantage of being ultra-

[0027] In this specification, the phrase "the molded article has excellent transparency" means that when the molded article is subjected to a transparency measurement described later in the Examples, the total light transmittance is 50.0% or more. That is, the molded article has the advantage that when the transparency measurement described later in the Examples is performed, the total light transmittance is 50.0% or more.

[0028] In addition, because the polymer microparticles contain bio-derived farnesene as an elastic body, they have the advantage of being able to significantly reduce the amount of plastic used in production. Such advantages also contribute to the achievement of Goal 12 "Ensure sustainable consumption and production patterns" and Goal 13 "Take urgent action to mitigate climate change and its impacts" of the Sustainable Development Goals (SDGs) advocated by the United Nations.

[0029] (1-1. Elastic body) An elastomer according to one embodiment of the present invention comprises farnesene units.

[0030] Farnesene is a bio-derived diene monomer produced from biomass such as sugar cane using fermentation technology.

[0031] The farnesene contained in the present elastomer may be α-farnesene, β-farnesene, or both α-farnesene and β-farnesene. Compared to α-farnesene, β-farnesene is easier to manufacture and therefore more readily available. Therefore, it is preferable that the farnesene contained in the present elastomer is β-farnesene.

[0032] The farnesene unit preferably comprises 70% by weight, more preferably 80% by weight, even more preferably 90% by weight, and particularly preferably 100% by weight of β-farnesene units, based on 100% by weight of the constituent units. This configuration has the advantage that the flowability of the resulting resin composition and the impact resistance and transparency of the resulting molded article are well balanced.

[0033] The elastic body preferably contains 5.0 to 99.9% by weight of farnesene units, more preferably 25.0 to 99.0% by weight, even more preferably 50.0 to 98.0% by weight, even more preferably 70.0 to 97.0% by weight, and particularly preferably 80.0 to 96.0% by weight, out of 100% by weight of the constituent units. This configuration has the advantage that the flowability of the resulting resin composition and the impact resistance and transparency of the resulting molded article are well balanced.

[0034] The elastomer preferably contains one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units, and polyfunctional units. This configuration has the advantage that the flowability of the resulting resin composition and the impact resistance and transparency of the resulting molded article are well balanced.

[0035] The elastomer preferably contains, in total, 0.1% by weight to 95.0% by weight, more preferably 1.0% by weight to 75.0% by weight, more preferably 2.0% by weight to 50.0% by weight, even more preferably 3.0% by weight to 30.0% by weight, and particularly preferably 4.0% by weight to 20.0% by weight of one or more kinds of constituent units selected from the group consisting of diene units other than farnesene units, vinyl units, and polyfunctional units, out of 100% by weight of constituent units. This configuration has the advantage that the fluidity of the resulting resin composition and the impact resistance and transparency of the resulting molded article are well balanced.

[0036] The elastomer preferably contains a diene unit other than the farnesene unit. When the elastomer contains a diene unit other than the farnesene unit, the resin composition containing the polymer microparticles can provide a molded article having excellent toughness and impact resistance. A molded article having excellent toughness and / or impact resistance can also be said to have excellent durability.

[0037] Examples of diene monomers from which the "diene units other than farnesene units" are derived include 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), and 2-chloro-1,3-butadiene. These diene monomers may be used alone or in combination of two or more. Compared with diene monomers other than farnesene and 1,3-butadiene, 1,3-butadiene is versatile and easily available. Therefore, 1,3-butadiene units are preferred as diene units other than farnesene units.

[0038] The diene monomer from which the "diene unit other than the farnesene unit" is derived can be referred to as a conjugated diene monomer. The elastomer preferably contains 0 to 95.0% by weight of diene units other than the farnesene unit, more preferably 1.0 to 95.0% by weight, even more preferably 5.0 to 95.0% by weight, and particularly preferably 10.0 to 95.0% by weight, of 100% by weight of the constituent units. This configuration has the advantage that the fluidity of the resulting resin composition and the impact resistance and transparency of the resulting molded article are well balanced.

[0039] The elastomer preferably contains a vinyl-based unit. According to this constitution, the obtained molded article has an advantage of being excellent in impact resistance and transparency. In this specification, the vinyl-based monomer means a monomer having only one vinyl group.

[0040] Examples of vinyl monomers from which vinyl units are derived include (a) vinyl arenes such as styrene, α-methylstyrene, monochlorostyrene, and dichlorostyrene; (b) vinyl carboxylic acids such as acrylic acid and methacrylic acid; (c) salts of the vinyl carboxylic acids (such as sodium acrylate); (d) esters of the vinyl carboxylic acids (such as alkyl (meth)acrylates); (e) vinyl cyanides such as acrylonitrile and methacrylonitrile; (f) vinyl halides such as vinyl chloride, vinyl bromide, and chloroprene; (g) vinyl acetate; and (h) alkenes such as ethylene, propylene, butylene, and isobutylene. The above-mentioned vinyl monomers may be used alone or in combination of two or more. In this specification, the term "alkyl (meth)acrylate" refers to a compound in which the portion other than the (meth)acrylate is composed only of an alkyl group.

[0041] Examples of esters of vinyl carboxylic acid include (a) alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (b) aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and phenyl (meth)acrylate; (c) hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; (d) glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; and (e) alkoxyalkyl (meth)acrylates. These (meth)acrylate monomers may be used alone or in combination of two or more. Among these (meth)acrylate monomers, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and butyl (meth)acrylate is more preferred. According to this configuration, the glass transition temperature (Tg) of the elastomer is lowered, so that polymer microparticles having a low Tg are obtained. As a result, (a) a resin composition containing the obtained polymer microparticles can provide a molded product having excellent toughness, and (b) the viscosity of the resin composition can be further reduced. In this specification, (meth)acrylate means acrylate and / or methacrylate.

[0042] The elastomer preferably contains a styrene unit and / or an alkyl (meth)acrylate unit. In other words, the elastomer preferably contains a styrene unit and / or an alkyl (meth)acrylate unit as a vinyl-based unit, and more preferably contains a styrene unit. This configuration has the advantage that the molded article obtained has excellent impact resistance and transparency.

[0043] The elastomer preferably contains a styrene unit as a vinyl-based unit. When the elastomer contains a styrene unit, the content of the styrene unit is preferably 20.0% by weight or less, more preferably 18.0% by weight or less, more preferably 15.0% by weight or less, even more preferably 12.0% by weight or less, and particularly preferably 10.0% by weight or less, based on 100% by weight of the constituent units of the elastomer. This configuration has the advantage that the obtained molded article has excellent impact resistance.

[0044] When the elastomer contains styrene units, the content of the styrene units is preferably 0.1% by weight or more, more preferably 1.0% by weight or more, more preferably 3.0% by weight or more, even more preferably 5.0% by weight or more, and particularly preferably 7.0% by weight or more, based on 100% by weight of the constituent units of the elastomer. This configuration has the advantage that the obtained molded article has excellent transparency.

[0045] The elastomer preferably contains 0 to 50.0% by weight of vinyl units, more preferably 1.0 to 30.0% by weight, even more preferably 3.0 to 20.0% by weight, and particularly preferably 5.0 to 15.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance and transparency.

[0046] The elastic body preferably contains 0 to 50.0% by weight of alkyl (meth)acrylate units, more preferably 0 to 45.0% by weight, even more preferably 0 to 40.0% by weight, and particularly preferably 0 to 35.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantages that the resulting resin composition has excellent fluidity and the resulting molded article has excellent impact resistance.

[0047] The elastic body preferably contains 0 to 50.0% by weight of styrene units and alkyl (meth)acrylate units, more preferably 1.0 to 30.0% by weight, even more preferably 3.0 to 20.0% by weight, and particularly preferably 5.0 to 15.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance and transparency.

[0048] The elastic body preferably contains a polyfunctional unit, which has the advantage that the dispersion stability of the polymer fine particles in the matrix resin can be maintained.

[0049] The polyfunctional monomer from which the polyfunctional unit is derived can be said to be a monomer having two or more radically polymerizable reactive groups in the same molecule. The radically polymerizable reactive group is preferably a carbon-carbon double bond. The polyfunctional monomer does not include butadiene, and examples thereof include (meth)acrylates having an ethylenically unsaturated double bond, such as allyl alkyl (meth)acrylates and allyloxy alkyl (meth)acrylates. Examples of monomers having two (meth)acrylic groups include ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, butane diol di(meth)acrylate, hexane diol di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. Examples of the polyethylene glycol di(meth)acrylates include triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and polyethylene glycol (600) di(meth)acrylate. Examples of monomers having three (meth)acrylic groups include alkoxylated trimethylolpropane tri(meth)acrylates, glycerol propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate. Examples of the alkoxylated trimethylolpropane tri(meth)acrylates include trimethylolpropane tri(meth)acrylate and trimethylolpropane triethoxy tri(meth)acrylate. Further, examples of monomers having four (meth)acrylic groups include pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, etc. Further, examples of monomers having five (meth)acrylic groups include dipentaerythritol penta(meth)acrylate, etc. Further, examples of monomers having six (meth)acrylic groups include ditrimethylolpropane hexa(meth)acrylate, etc.Polyfunctional monomers also include diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, divinylbenzene, and the like.

[0050] The polyfunctional unit is not particularly limited, but is preferably one or more selected from the group consisting of butylene glycol di(meth)acrylate unit, allyl (meth)acrylate unit and divinylbenzene unit, and more preferably butylene glycol di(meth)acrylate unit. This configuration has the advantage that the fluidity of the resulting resin composition and the impact resistance and transparency of the resulting molded product are well balanced.

[0051] The elastic body preferably contains 0 to 20.0% by weight of the polyfunctional unit, more preferably 0.1 to 15.0% by weight, even more preferably 0.5 to 13.0% by weight, and particularly preferably 1.0 to 10.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance and transparency.

[0052] The elastic body preferably contains 20.0% by weight or less of polyfunctional units, more preferably 15.0% by weight or less, more preferably 13.0% by weight or less, even more preferably 10.0% by weight or less, even more preferably 7.0% by weight or less, and particularly preferably 5.0% by weight or less, based on 100% by weight of the constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance.

[0053] (Volume average particle size of elastic body) The volume average particle diameter of the elastic body is less than 50 nm, preferably 10 nm to 49 nm, more preferably 10 nm to 48 nm, even more preferably 15 nm to 40 nm, and particularly preferably 15 nm to 33 nm. When the volume average particle diameter of the elastic body is (a) 10 nm or more, an elastic body having a desired volume average particle diameter can be obtained, and when it is (b) less than 50 nm, the transparency and impact resistance of the obtained molded body are good. The volume average particle diameter of the elastic body can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the elastic body as a sample. The method for measuring the volume average particle diameter of the elastic body will be described in detail in the following examples.

[0054] (Ratio of elastic body) The proportion of the elastomer in the polymer microparticles is preferably 40 to 97% by weight, more preferably 50 to 95% by weight, and even more preferably 50 to 90% by weight, based on 100% by weight of the entire polymer microparticles. When the proportion of the elastomer is 40% by weight or more, the resin composition can provide a molded article having excellent toughness and impact resistance. When the proportion of the elastomer is 97% by weight or less, the polymer microparticles do not easily aggregate (are unlikely to aggregate), and therefore the dispersibility in the resin composition is good. As a result, the resin composition has an excellent balance of physical properties.

[0055] The proportion of the elastomer in the polymer microparticles is preferably 90% by weight or less, more preferably 80% by weight or less, still more preferably 70% by weight or less, even more preferably 65% ​​by weight or less, and particularly preferably 60% by weight or less, based on 100% by weight of the entire polymer microparticles. This configuration has the advantage that the obtained molded article has excellent transparency.

[0056] In addition, the "elastic body" of the polymer microparticles is composed of elastomer 1, elastomer 2, ..., and elastomer 3, which are polymerized separately. n The "elastic body" of the polymer microparticles may include elastomer 1, elastomer 2, ..., and elastomer nmay include one elastomer obtained by sequentially polymerizing each of the elastomers. In this way, an elastomer (multistage polymerized elastomer) may be produced by multistage polymerization in which a plurality of elastomers (polymers) are sequentially polymerized. In the multistage polymerized elastomer, each of the plurality of elastomers may form a layer structure. In this way, a multistage polymerized elastomer in which each of the plurality of elastomers forms a layer structure can also be called a multilayered elastomer. That is, in one embodiment of the present invention, the "elastic body" of the polymer microparticles may include (a) a composite of a plurality of elastomers, (b) a multistage polymerized elastomer, and / or (c) a multilayered elastomer.

[0057] (1-2. Graft part) The polymer microparticles according to one embodiment of the present invention have a graft portion grafted to the elastomer. In this specification, the polymer grafted to the elastomer and the polymer grafted to the polymer grafted to the elastomer are referred to as the graft portion. The graft portion is not particularly limited, but preferably contains, as a constituent unit, a constituent unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, vinyl cyan monomers, and (meth)acrylate monomers. Since the graft portion has the above-mentioned structure, it can play various roles. The "various roles" are, for example, (a) improving the compatibility between the resin component in the resin composition and the polymer microparticles, (b) improving the dispersibility of the polymer microparticles in the resin composition and in the molded body, and (c) enabling the polymer microparticles to be dispersed in the form of primary particles in the resin composition and in the molded body, and (d) improving the powder properties of the powder particles.

[0058] A powder or granule having excellent powder characteristics has the advantage that the powder or granule can be mixed well with a matrix resin to be mixed. In particular, when a powder-like matrix resin such as polyvinyl chloride (PVC) is mixed with a powder or granule in order to modify the powder-like matrix resin such as polyvinyl chloride (PVC), it is preferable to use a powder or granule having excellent powder characteristics.

[0059] Specific examples of aromatic vinyl monomers include styrene, α-methylstyrene, p-methylstyrene, and divinylbenzene.

[0060] Specific examples of vinyl cyanide monomers include acrylonitrile and methacrylonitrile.

[0061] Specific examples of the (meth)acrylate monomer include the same monomers as the alkyl (meth)acrylate monomers described above.

[0062] The one or more monomers selected from the group consisting of the aromatic vinyl monomer, the vinyl cyan monomer, and the (meth)acrylate monomer may be used alone or in combination of two or more.

[0063] The graft portion preferably contains aromatic vinyl units, vinylcyan units and (meth)acrylate units in a total amount of 10% by weight to 100% by weight, more preferably 30% by weight to 100% by weight, more preferably 50% by weight to 100% by weight, particularly preferably 60% by weight to 100% by weight, and most preferably 70% by weight to 100% by weight, based on 100% by weight of all constituent units. This configuration has the advantage that the resulting molded article has excellent impact resistance and transparency.

[0064] The graft portion preferably contains 10.0 to 80.0% by weight of (meth)acrylate units, more preferably 15.0 to 75.0% by weight, even more preferably 20.0 to 70.0% by weight, and particularly preferably 30.0 to 60.0% by weight, based on 100% by weight of the structural units. This configuration has the advantage of providing good compatibility with the matrix resin.

[0065] The graft moiety preferably contains a styrene unit, which has the advantage that the obtained molded article has excellent transparency.

[0066] When the graft portion contains a styrene unit, the content of the styrene unit is preferably 10.0 to 80.0% by weight, more preferably 15.0 to 75.0% by weight, more preferably 20.0 to 70.0% by weight, even more preferably 25.0 to 70.0% by weight, and particularly preferably 30.0 to 70.0% by weight, based on 100% by weight of the constituent units of the graft portion. This configuration has the advantage that the obtained molded article has excellent transparency.

[0067] It is preferred that the elastomer does not contain a styrene unit and the graft portion contains a styrene unit, which has the advantage that the flexibility of the elastomer is maintained and the resulting molded article has excellent impact resistance.

[0068] It is preferred that the elastomer contains a styrene unit and the graft portion contains a styrene unit, which has the advantage that the obtained molded article has excellent transparency.

[0069] When the elastomer contains a styrene unit and the graft portion is composed of a multi-stage polymerization graft portion described later, 2n-1 (n is an integer of 1 or more) preferably does not contain a styrene unit, 2n (n is an integer of 1 or more) preferably contains a styrene unit. This configuration has the advantages of providing a molded article with excellent transparency and providing excellent stability of the latex particles during polymerization.

[0070] When the elastomer does not contain a styrene unit and the graft portion is composed of a multi-stage polymerization graft portion described later, 2n-1 (n is an integer of 1 or more) preferably contains a styrene unit, 2n (n is an integer of 1 or more) preferably does not contain a styrene unit. This configuration has the advantages that the molded product has excellent transparency and the compatibility between the polymer fine particles and the matrix resin is improved.

[0071] The graft portion may contain a polyfunctional unit as a constituent unit. When the graft portion contains a polyfunctional unit, it has the following advantages: (a) swelling of the polymer fine particles in the resin composition can be prevented, (b) the powder state of the polymer fine particles is improved, and the handleability of the resin composition tends to be improved, and (c) the dispersibility of the polymer fine particles in the resin composition and / or the compatibility between the matrix resin and the polymer fine particles are improved.

[0072] When the graft portion contains a polyfunctional unit, the resin composition can provide a molded article having superior toughness and impact resistance, as compared with a case in which the graft portion does not contain a polyfunctional unit.

[0073] The polyfunctional monomer that can be used in the polymerization of the graft portion includes the same monomers as the polyfunctional monomers described above.

[0074] (Proportion of graft area) The proportion of the graft portion in the polymer microparticles is preferably 10 to 70% by weight, more preferably 15 to 60% by weight, and even more preferably 20 to 50% by weight, based on 100% by weight of the entire polymer microparticles. When the proportion of the graft portion is 10% by weight or more, the powder state of the polymer microparticles is advantageously good. When the proportion of the elastomer is 70% by weight or less, the impact resistance of the resulting molded article is advantageously good.

[0075] The graft portion is composed of graft portion 1, graft portion 2, . . . and graft portion n The graft portion may include a composite of graft portion 1, graft portion 2, ..., and graft portion n In this manner, a multi-stage polymerization graft portion may be produced by multi-stage polymerization of a plurality of types of graft portions.

[0076] When the graft portion is composed of multiple types of graft portions, not all of these multiple types of graft portions need to be graft-bonded to the elastomer. At least a portion of at least one type of graft portion may be graft-bonded to the elastomer, and the other types (multiple other types) of graft portions may be graft-bonded to the graft portion graft-bonded to the elastomer.

[0077] Graft portion 1, graft portion 2, ..., and graft portion n In the multi-stage polymerization graft portion, n The graft part n-1 or a graft portion. n-1 In the multi-stage polymerization graft portion, n Part of the graft n-1 Sometimes it penetrates inside the

[0078] In the multi-stage polymerization graft portion, each of the multiple graft portions may form a layer structure. For example, when the multi-stage polymerization graft portion is composed of graft portions 1, 2, and 3, an embodiment in which graft portion 1 forms the innermost layer in the graft portion, a layer of graft portion 2 is formed on the outer side of graft portion 1, and a layer of graft portion 3 is formed as the outermost layer on the outer side of the layer of graft portion 2 is also one aspect of the present invention. In this way, a multi-stage polymerization graft portion in which each of the multiple graft portions forms a layer structure can also be called a multi-layer graft portion. That is, in one embodiment of the present invention, the graft portion may include (a) a mixture of multiple types of graft portions, (b) a multi-stage polymerization graft portion, and / or (c) a multi-layer graft portion.

[0079] When the elastomer and the graft portion are polymerized in this order in the production of polymer microparticles, at least a portion of the graft portion can cover at least a portion of the elastomer in the resulting polymer microparticles. Polymerization of the elastomer and the graft portion in this order can be said to be multistage polymerization of the elastomer and the graft portion. The polymer microparticles obtained by multistage polymerization of the elastomer and the graft portion can also be said to be multistage polymers.

[0080] When the polymer microparticles are multi-stage polymers, the graft portion may cover at least a portion of the elastomer, or may cover the entire elastomer. When the polymer microparticles are multi-stage polymers, a portion of the graft portion may penetrate into the inside of the elastomer.

[0081] When the polymer microparticles are multistage polymers, the elastomer and the graft portion may form a layer structure. For example, an embodiment in which the elastomer forms the innermost layer (also referred to as a core layer) and the layer of the graft portion is formed as the outermost layer (also referred to as a shell layer) on the outside of the elastomer is also one aspect of the present invention. A structure in which the elastomer is the core layer and the graft portion is the shell layer can also be called a core-shell structure. Thus, polymer microparticles in which the elastomer and the graft portion form a layer structure (core-shell structure) can also be called multilayer polymers or core-shell polymers. That is, in one embodiment of the present invention, the polymer microparticles may be multistage polymers and / or multilayer polymers or core-shell polymers. However, as long as the graft portion is graft-bonded to the elastomer, the polymer microparticles are not limited to the above structure.

[0082] At least a portion of the graft portion preferably covers at least a portion of the elastomer, in other words, at least a portion of the graft portion preferably exists on the outermost side of the polymer fine particle.

[0083] (1-3. Physical properties of polymer particles) The physical properties of the polymer fine particles will be described below.

[0084] (Volume average particle size of polymer particles) The volume average particle diameter of the polymer microparticles is not particularly limited, but is preferably less than 50 nm, more preferably 10 nm to 49 nm, more preferably 10 nm to 48 nm, even more preferably 15 nm to 40 nm, and particularly preferably 15 nm to 33 nm. When the volume average particle diameter of the polymer microparticles is within the above range, there is an advantage that the dispersibility of the polymer microparticles in the resin composition is good and the transparency of the molded product is improved. In this specification, the "volume average particle diameter of the polymer microparticles" refers to the volume average particle diameter of the primary particles of the polymer microparticles, unless otherwise specified. The volume average particle diameter of the polymer microparticles can be measured using a dynamic light scattering particle size distribution measuring device or the like, using an aqueous latex containing the polymer microparticles as a sample. The volume average particle diameter of the polymer microparticles will be described in detail in the following examples. The volume average particle diameter of the polymer microparticles can also be measured by cutting a molded product of the resin composition, photographing the cut surface using an electron microscope or the like, and using the obtained imaging data (photographed image).

[0085] (1-4. Method for producing polymer microparticles) The polymer fine particles can be produced by polymerizing an elastomer, and then graft polymerizing a polymer that constitutes a graft moiety onto the elastomer in the presence of the elastomer.

[0086] (Method of manufacturing elastic body) The elastomer can be produced by, for example, emulsion polymerization, suspension polymerization, microsuspension polymerization, or the like. The elastomer can also be produced by, for example, a method of polymerizing a monomer containing farnesene such that the increase in the polymerization conversion rate is 20% or less per hour. For example, a method of adding paramenthane hydroperoxide, which is a polymerization initiator, in equal amounts immediately after the lump-sum addition of other components used in the production of the elastomer (0 hours after the lump-sum addition) and in 10 portions at 1-hour intervals after the lump-sum addition can be mentioned.

[0087] (Method of manufacturing the graft part) The graft portion can be formed, for example, by polymerizing the monomer used for forming the graft portion by known radical polymerization. When (a) the elastomer or (b) the polymer microparticle precursor containing the elastomer is obtained as an aqueous latex, the polymerization of the graft portion is preferably carried out by emulsion polymerization. The graft portion can be produced, for example, according to the method described in WO2005 / 028546.

[0088] The graft portion is a portion having a plurality of types of graft portions (e.g., graft portion 1, graft portion 2, ..., graft portion n A method for producing a graft portion in the case where the graft portion is composed of graft portion 1, graft portion 2, ..., graft portion n may be polymerized separately by the above-mentioned method, and then mixed and composited to produce a graft portion (composite) consisting of a plurality of types of graft portions. Alternatively, graft portion 1, graft portion 2, ..., graft portion n may be sequentially polymerized in multiple stages to produce one graft moiety consisting of multiple types of graft moieties.

[0089] When emulsion polymerization is employed as a method for producing polymer fine particles, a known emulsifier (dispersant) can be used for producing the polymer fine particles.

[0090] Examples of emulsifiers include anionic emulsifiers, nonionic emulsifiers, polyvinyl alcohol, alkyl-substituted cellulose, polyvinylpyrrolidone, polyacrylic acid derivatives, etc. Examples of anionic emulsifiers include sulfur-based emulsifiers, phosphorus-based emulsifiers, sarcosinic acid-based emulsifiers, carboxylic acid-based emulsifiers, etc. Examples of sulfur-based emulsifiers include sodium dodecylbenzenesulfonate (abbreviation: SDBS), sodium lauryl sulfate, etc. Examples of phosphorus-based emulsifiers include sodium polyoxyethylene lauryl ether phosphate, tripotassium phosphate, etc.

[0091] When the emulsion polymerization method is used as the method for producing the polymer microparticles, a thermally decomposable initiator can be used for producing the polymer microparticles. Examples of the thermally decomposable initiator include known initiators such as 2,2'-azobisisobutyronitrile and (b) peroxides such as organic peroxides and inorganic peroxides. Examples of the organic peroxides include t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, and t-hexyl peroxide. Examples of the inorganic peroxides include hydrogen peroxide, potassium persulfate, and ammonium persulfate.

[0092] A redox type initiator can also be used to produce polymer microparticles. The redox type initiator is an initiator that uses (a) a peroxide such as an organic peroxide or an inorganic peroxide in combination with (b) a transition metal salt such as ferrous sulfate (FeSO4·7H2O), or a reducing agent such as sodium formaldehyde sulfoxylate or glucose. If necessary, a chelating agent such as disodium ethylenediaminetetraacetate, and if necessary, a phosphorus-containing compound such as sodium pyrophosphate, may also be used in combination.

[0093] When a redox type initiator is used, polymerization can be performed even at a low temperature where the peroxide does not substantially decompose thermally, and the polymerization temperature can be set in a wide range. Therefore, it is preferable to use a redox type initiator. Among redox type initiators, redox type initiators using organic peroxides such as cumene hydroperoxide, dicumyl peroxide, paramenthane hydroperoxide, and t-butyl hydroperoxide as peroxides are preferable. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, chelating agent, etc. used when a redox type initiator is used can be within a known range.

[0094] When a polyfunctional monomer is used in the polymerization of the elastomer or the graft portion for the purpose of introducing a crosslinked structure into the elastomer or the graft portion, a known chain transfer agent can be used in a known amount range. By using the chain transfer agent, the molecular weight and / or degree of crosslinking of the obtained elastomer or the graft portion can be easily adjusted.

[0095] In the production of the polymer microparticles, in addition to the above-mentioned components, a surfactant may be used. The type and amount of the surfactant used are within the known ranges.

[0096] In the production of polymer microparticles, the polymerization conditions such as polymerization temperature, pressure, and deoxidation may be appropriately set within known numerical ranges.

[0097] As described above, the polymer microparticles can provide a resin composition having excellent fluidity. In addition, as described below, the polymer microparticles can be mixed with polyvinyl chloride (PVC) to provide a resin composition capable of providing a molded article having excellent impact resistance. In other words, the polymer microparticles can be suitably used as a modifier for polyvinyl chloride. Therefore, one embodiment of the present invention can be said to be a modifier for polyvinyl chloride.

[0098] An embodiment of the present invention may be configured as follows: The elastic body has a graft portion grafted to the elastic body, A modifier for polyvinyl chloride, wherein the graft portion contains alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more, based on 100% by weight of constituent units.

[0099] [2. Powder] A powder according to one embodiment of the present invention (hereinafter, sometimes referred to as "the present powder") contains the polymer microparticles described in the above section [1. Polymer microparticles]. Because the present powder has the above-mentioned constitution, it has the advantage of being able to provide a resin composition with excellent fluidity and a molded article with excellent impact resistance and transparency. For example, a resin composition can be obtained by blending (adding) the present powder to any resin. A molded article obtained by molding the resin composition has the advantage of excellent impact resistance and transparency. Furthermore, because the present powder has the above-mentioned constitution, it also has the advantage of excellent powder properties.

[0100] In this specification, the term "particulate material" includes both powder and granules, and refers to an aggregate of powder, granules, etc. In addition, when making a particular distinction, "powder" refers to a material having a volume average particle diameter of 0.01 mm to 0.1 mm, and "granules" refers to a material having a volume average particle diameter of 0.1 mm to 10 mm. However, the particulate material may contain coarse particles of 10 mm or more. The "volume average particle diameter" in the range of less than 10 μm can be measured using a dynamic light scattering (DLS) particle size distribution analyzer Nanotrac WaveII-EX150 (manufactured by Microtrack Bell Co., Ltd.), and the "volume average particle diameter" in the range of 10 μm or more can be measured using a laser diffraction particle size distribution analyzer Microtrack MT3000II (manufactured by Microtrack Bell Co., Ltd.).

[0101] (2-1. Other optional ingredients) The powder may contain optional components other than the polymer microparticles, as necessary. Examples of the optional components include curing agents, colorants such as pigments and dyes, extender pigments, pigment dispersants, UV absorbers, the above-mentioned antioxidants, heat stabilizers (gelling inhibitors), plasticizers, leveling agents, defoamers, silane coupling agents, antistatic agents, flame retardants, lubricants, viscosity reducers, viscosity adjusters, thixotropic agents, low-shrinkage agents, inorganic fillers, organic fillers, thermoplastic resins, drying agents, dispersants, thermal conductivity improvers, water binding agents, anti-sagging agents, color separation inhibitors, anti-settling agents, coating wear adjusters, surface adjusters, monobasic organic acids, camphor, castor oil, etc.

[0102] These other optional components can be added at any stage in the production of the powder or granule. For example, they may be added during the production (polymerization) of the polymer microparticles, they may be added to the aqueous latex of the polymer microparticles, or they may be added to the powder or granule.

[0103] (2-2. Manufacturing method of powder and granular materials) The method for producing the powder or granule of the present invention is not particularly limited as long as it can produce a powder or granule containing fine polymer particles. For example, the following embodiments are preferred: A preparation step of preparing polymer microparticles; an aggregating step of aggregating the polymer fine particles; a drying step of drying the aggregate obtained in the aggregation step.

[0104] (Preparation process) Specific examples of the preparation process are the same as those described in the above section (1-4. Method for producing polymer microparticles), and therefore the description is incorporated herein by reference and will not be described here.

[0105] (Agglutination process) The aggregation step is not particularly limited as long as it can finally obtain an aggregate of polymer fine particles.

[0106] The method of aggregating the polymer microparticles is not particularly limited. Examples of the method of aggregating the polymer microparticles include known methods such as a method using a coagulant, a method using a solvent, and a method of spraying an aqueous latex of polymer microparticles. Here, the mixture containing the aggregate of polymer microparticles and the aqueous solvent obtained by aggregating the polymer microparticles in the aqueous latex is also called a slurry.

[0107] As a method for aggregating the polymer fine particles, it is preferable to adopt a method using a coagulant, in other words, it is preferable to use a coagulant in the aggregating step.

[0108] Examples of the coagulant include an aqueous solution of an inorganic salt, an aqueous solution of an inorganic acid, an aqueous solution of an organic salt, an aqueous solution of an organic acid, and a polymeric coagulant.

[0109] Examples of inorganic salts include chloride salts, bromide salts, iodide salts, sulfate salts, nitrate salts, ammonium salts, and phosphate salts. Specific examples of inorganic salts include sodium chloride, potassium chloride, lithium chloride, sodium bromide, potassium bromide, lithium bromide, potassium iodide, sodium iodide, potassium sulfate, sodium sulfate, ammonium sulfate, ammonium chloride, sodium nitrate, potassium nitrate, calcium chloride, ferrous sulfate, magnesium sulfate, zinc sulfate, copper sulfate, barium chloride, ferrous chloride, ferric chloride, magnesium chloride, ferric sulfate, aluminum sulfate, potassium alum, and iron alum.

[0110] Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0111] The coagulant may be used alone or in combination of two or more. As the coagulant, an aqueous solution of a monovalent or divalent inorganic salt or an inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be suitably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, in portions, or continuously.

[0112] As the coagulant, only one of the above-mentioned compounds may be used, or two or more of them may be used in combination. As the coagulant, among the above-mentioned compounds, an aqueous solution of monovalent or divalent inorganic salt or inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be preferably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, added in portions, or added continuously.

[0113] In one embodiment of the present invention, the polymer microparticles can be aggregated by contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant (e.g., an aqueous solution). The method of contacting the aqueous latex containing the polymer microparticles with the coagulant or the solution of the coagulant is not particularly limited. Examples of the method include (i) a method of contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant, and (ii) (ii-a) a method of contacting droplets containing polymer microparticles obtained by spraying the aqueous latex containing the polymer microparticles with (ii-b) a coagulant or a solution of the coagulant, or a solution of the coagulant solution.

[0114] In one embodiment of the present invention, a slurry containing agglomerates of polymeric particles can be obtained by contacting an aqueous latex containing polymeric particles with a coagulant or a solution of a coagulant.

[0115] In the course of intensive research, the present inventor independently and surprisingly found that a powdery or granular material having excellent powder characteristics can be obtained by setting the temperature (aggregation temperature) at which the aqueous latex containing polymer fine particles is brought into contact with a coagulant or a solution of the coagulant to be below room temperature (for example, 5°C to 10°C). Conventionally, room temperature (for example, 23°C) has been used as the aggregation temperature of polymer fine particles. This is because the higher the temperature, the better the aggregation efficiency of the polymer fine particles. However, according to the knowledge found by the present inventor, a powdery or granular material having excellent powder characteristics can be obtained by setting the aggregation temperature to be below room temperature. This knowledge can be said to be knowledge that could not be predicted from the conventional technology in which a temperature higher than room temperature was used as the aggregation temperature.

[0116] In one embodiment of the present invention, the aggregation temperature in the aggregation step is preferably 23° C. or lower, more preferably 20° C. or lower, further preferably 15° C. or lower, and particularly preferably 10° C. or lower.

[0117] From the viewpoint of aggregation efficiency of the polymer microparticles, the aggregation temperature in the aggregation step is preferably 0°C or higher, more preferably 1°C or higher, further preferably 3°C or higher, and particularly preferably 5°C or higher.

[0118] The aggregating step may further include a heat treatment step of heat-treating (heating) the slurry. By carrying out the heat treatment step, it is possible to obtain a powder having more excellent powder properties.

[0119] Since a powder having even more excellent powder properties can be obtained, the temperature of the slurry in the heat treatment step (heat treatment temperature) is preferably 70° C. or higher, more preferably 75° C. or higher, and even more preferably 80° C. or higher. The temperature of the slurry in the heat treatment step (heat treatment temperature) is preferably less than 100° C., more preferably 95° C. or lower, and even more preferably 90° C. or lower.

[0120] In the heat treatment step, the time for which the slurry is held at the heat treatment temperature is referred to as the “heat treatment time.” Since a powder having even more excellent powder properties can be obtained, the heat treatment time of the slurry in the heat treatment step is preferably 5 to 120 seconds, more preferably 5 to 60 seconds, even more preferably 5 to 40 seconds, and particularly preferably 5 to 20 seconds.

[0121] The agglomeration step may further include a recovery step of recovering the resulting agglomerates from the slurry.

[0122] The recovery step is not particularly limited as long as it can separate the aqueous solvent of the slurry from the aggregates, and any known method can be used. Examples of the recovery step include a method of filtering the slurry and a method of centrifugal dehydration of the slurry.

[0123] When a heat treatment step is performed, it is preferable to cool the slurry after the heat treatment step to room temperature (e.g., 23°C) and then recover the aggregates from the slurry. When the slurry is at room temperature (e.g., 23°C), filtration of the slurry and / or dehydration from the slurry becomes easy. As a result, a powder having even more excellent powder properties can be obtained.

[0124] (drying process) The drying step is a step of drying the aggregate of polymer microparticles obtained by the above-mentioned aggregation step. The method for drying the aggregate is not particularly limited, and examples thereof include static drying, flash drying, and freeze drying.

[0125] In this specification, the term "static drying" refers to a mode in which an aggregate of polymer fine particles is dried by being statically left in a container such as an oven.

[0126] In this specification, the term "airflow drying" refers to a mode in which the aggregates are dried while being airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while being airborne in the container.

[0127] In this specification, the term "airflow drying" refers to drying the aggregates while they are airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while they are airborne in the container.

[0128] The method of freeze-drying is not particularly limited, and any conventionally known method can be used. When freeze-drying is used as the drying step, the drying step can be easily carried out at 0° C. or lower.

[0129] (Cleaning process) Between the aggregating step and the drying step, a washing step of washing the aggregate obtained in the aggregating step with washing water (for example, tap water, ion-exchanged water or pure water) may be further included.

[0130] As described below, the present powder can be mixed with polyvinyl chloride (PVC) to provide a resin composition that can provide a molded article with excellent impact resistance. In other words, the present powder can be suitably used as a modifier for polyvinyl chloride.

[0131] An embodiment of the present invention may be configured as follows: The elastic body has a graft portion grafted to the elastic body, The graft portion contains alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more based on 100% by weight of the structural units, A granular polyvinyl chloride modifier.

[0132] [3. Resin composition] A resin composition containing the polymer fine particles described in the above section [1. Polymer fine particles] and a matrix resin, or a resin composition containing the powder particles described in the above section [2. Powder particles] and a matrix resin is also one embodiment of the present invention. Since this resin composition has the above-mentioned configuration, it has the advantage of being able to provide a molded product that is excellent in flowability, impact resistance, and transparency.

[0133] (Matrix resin) Examples of the matrix resin include thermoplastic resins such as acrylic polymers, vinyl copolymers, polycarbonates, polyamides, polyesters, polyphenylene ethers, polyurethanes, and polyvinyl acetates, etc. These may be used alone or in combination of two or more.

[0134] The acrylic polymer is a polymer mainly composed of a structural unit made of an acrylic acid ester monomer. The acrylic acid ester monomer preferably has an ester moiety having 1 to 20 carbon atoms. Examples of the acrylic polymer include (a) a homopolymer of an acrylic acid ester monomer, and (b) a copolymer of an acrylic acid ester monomer with a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, or vinyl acetate, or a vinyl copolymer (hereinafter also referred to as an acrylic copolymer).

[0135] The vinyl copolymer is obtained by copolymerizing a mixture of vinyl monomers containing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a cyanide vinyl monomer, and an unsaturated carboxylic acid alkyl ester monomer. The mixture of vinyl monomers may further contain other monomers copolymerizable with the above-mentioned monomers.

[0136] Specific examples of vinyl copolymers include polyvinyl chloride (PVC), chlorinated polyvinyl chloride, polystyrene, styrene-acrylonitrile copolymer, styrene-acrylonitrile-N-phenylmaleimide copolymer, α-methylstyrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene copolymer, etc. These may be used alone or in combination of two or more.

[0137] Examples of polyesters include polyethylene terephthalate and polybutylene terephthalate, etc. In addition, examples of the polyesters include aliphatic polyesters, plant-derived resins such as polylactic acid, and biodegradable resins.

[0138] The matrix resin is more preferably polyvinyl chloride. This configuration has the advantage that it is possible to provide a resin composition having excellent flowability and a molded article having excellent impact resistance and transparency.

[0139] (Other optional ingredients) The resin composition may contain optional components other than the matrix resin, as necessary. Examples of the optional components include curing agents, colorants such as pigments and dyes, extender pigments, pigment dispersants, ultraviolet absorbers, the above-mentioned antioxidants, heat stabilizers (gelling inhibitors), plasticizers, leveling agents, defoamers, silane coupling agents, antistatic agents, flame retardants, lubricants, viscosity reducers, viscosity adjusters, thixotropic agents, low-shrinkage agents, inorganic fillers, organic fillers, thermoplastic resins, drying agents, dispersants, thermal conductivity improvers, water binding agents, anti-sagging agents, color separation inhibitors, anti-settling agents, coating wear adjusters, surface adjusters, monobasic organic acids, camphor, castor oil, etc.

[0140] (Fluidity of Resin Composition) The flow rate of the resin composition is 10.0 (cm 3 / sec×10 -2 ), and preferably greater than 12.0 (cm 3 / sec×10 -2 ) or more, and 14.0 (cm 3 / sec×10 -2 ) or more. According to this configuration, it can be said that the resin composition has excellent fluidity. The method for measuring the flow rate of the resin composition by method B will be described in detail in the examples below.

[0141] (Method of producing resin composition) The method for producing a resin composition according to one embodiment of the present invention includes a step of mixing the polymer fine particles described in the section [1. Polymer fine particles] with a matrix resin. According to this configuration, a resin composition in which the polymer fine particles are uniformly dispersed in the matrix resin can be obtained.

[0142] Regarding the method for producing the resin composition, various components and specific steps are not particularly limited, and the above explanations are appropriately used.

[0143] The specific method for mixing the powder and the matrix resin is not particularly limited, and examples of the method include a method using a rotation / revolution mixer, a planetary mixer, a disperser, etc. A preferred method for mixing the polymer fine particles and the matrix resin is, for example, a method in which the polymer fine particles and the matrix resin are mixed using a rotation / revolution mixer at 2000 rpm for 40 minutes.

[0144] Furthermore, the method for producing the resin composition may include a step of washing the obtained resin composition. By washing the resin composition, a resin composition containing fewer impurities can be produced.

[0145] Furthermore, the method for producing a resin composition according to one embodiment of the present invention may include other steps. In addition to the above-mentioned steps, the method may include a step of heating the obtained resin composition and devolatilizing and drying it. Various methods can be used for such a step, and there is no particular limitation. Examples of the step of devolatilizing and drying include heating and vacuum devolatilization.

[0146] [4. Molded body] A molded article obtained by molding the resin composition described in the above section [3. Resin composition] is also one embodiment of the present invention. The molded article has the advantages of excellent impact resistance and transparency.

[0147] (Impact resistance of molded body) The IZOD test result for the molded product at 23°C was 32.1 kJ / m 2 More preferably, it is greater than 40.0 kJ / m 2 More preferably, it is 50.0 kJ / m or more. 2 More preferably, it is 60.0 kJ / m or more. 2 More preferably, it is 70.0 kJ / m or more. 2 More preferably, it is 75.0 kJ / m or more. 2 More preferably, it is 80.0 kJ / m or more. 2It is particularly preferable that the impact resistance is 10.0 kJ / m or more. According to this constitution, it can be said that the molded article has excellent impact resistance. In addition, the result of the IZOD test of the molded article at 0°C is, but is not particularly limited to, 10.0 kJ / m 2 It is preferable that the concentration is 12.0 kJ / m or more. 2 More preferably, it is 15.0 kJ / m or more. 2 More preferably, it is 20.0 kJ / m or more. 2 The measurement method of the IZOD test of the molded product at 23° C. or 0° C. will be described in detail in the Examples below.

[0148] (Transparency of Molded Product) The total light transmittance of the molded body is preferably 50.0% or more, more preferably 51.0% or more, more preferably 55.0% or more, even more preferably 60.0% or more, and particularly preferably 65.0% or more. According to this configuration, the molded body can be said to have excellent transparency. In addition, the turbidity of the molded body is not particularly limited, but is preferably 60% or less, more preferably 55% or less, even more preferably 40% or less, and particularly preferably 30% or less. The method for measuring the total light transmittance and the method for measuring the turbidity of the molded body will be described in detail in the examples described later.

[0149] (Method of Manufacturing Molded Product) In the method for producing a molded article according to one embodiment of the present invention, the molded article can be obtained by molding the resin composition described in the section [2. Resin composition].

[0150] The method for producing the present molded article is not particularly limited, but examples thereof include a rolling and / or pressing method, an extrusion molding method, and an injection molding method. EXAMPLES

[0151] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto. One embodiment of the present invention can be practiced with appropriate modifications within the scope of the above or below-mentioned purpose, and all of these modifications are included in the technical scope of the present invention. In the following, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".

[0152] First, various measurement and evaluation methods will be described.

[0153] [Measurement and evaluation methods] (Measurement of volume average particle size) The volume average particle size was measured on a volume basis using a particle size distribution measuring device using dynamic light scattering ("Nanotrac Wave-EX150" manufactured by Nikkiso Co., Ltd.).

[0154] (Preparation of test pieces for measuring transparency and impact resistance) 100 parts of polyvinyl chloride (Kaneka Corporation, "Kanevinyl S-1007") as a matrix resin, 1.0 part of a tin-based stabilizer (Nitto Kasei Corporation, "TVS#8831"), 0.8 parts of a lubricant (Emery Oleochemicals Japan, Inc., "Loxiol GH-4"), and 0.2 parts of a lubricant (Clariant Japan, Inc., "Wax-E") were heated to 110°C with stirring and cooled to room temperature (23°C) to obtain a mixture (total amount 102.0 parts).

[0155] To the resulting mixture, 10 parts of polymer fine particles (impact modifier) ​​obtained in the following Examples or Comparative Examples were added per 100 parts of polyvinyl chloride to obtain a resin composition. The resin composition was kneaded for 5 minutes at 155°C using two rolls ("8-inch mixing rolls" manufactured by Nippon Roll Mfg. Co., Ltd.) to produce a sheet (molded product). Thereafter, the resin composition was kneaded at 180°C and 70 kgf / cm using a heat press machine (37-ton press manufactured by Shinto Metal Works, Ltd.). 2The sheet was cut to prepare a test piece for measuring impact resistance (thickness 5 mm) and a test plate for measuring transparency (30 mm x 40 mm x thickness 5 mm). The obtained test piece for measuring impact resistance complies with the JIS K 7110 standard.

[0156] (Measurement of impact resistance) An IZOD test was performed on an impact resistance test piece (thickness 5 mm) with a V notch at 23°C or 0°C to measure the impact resistance in accordance with JIS K 7110.

[0157] (Transparency measurement) The total light transmittance (TT, %) and haze (turbidity) (Haze, %) of a transparency test plate (5 mm) were measured in accordance with JIS K 6714.

[0158] (Measurement of B method flow) The resin composition was filled into a cylinder at room temperature and 190°C, and a load of 300 kgf / cm was applied from a die: 1 mmφ×10 mm. 2 By extruding at 100°C, the amount of resin composition discharged from the die (cm 3 ) was measured. 3 ) to the discharge volume (cm 3 ) by the time (s) required for the material to be discharged from the die, yielding the flow rate (cm 3 / sec×10 -2 ) was calculated.

[0159] The results obtained are shown in Table 2.

[0160] Example 1 <Manufacturing of Elastic Body> 200 parts of water, 0.2 parts of tripotassium phosphate, and 5 parts of sodium lauryl sulfate were charged into a polymerization vessel equipped with a stirrer, and after replacing with nitrogen, the temperature was raised to 60°C. 0.0094 parts of ferrous sulfate (FeSO4·7H2O), 0.0156 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.5 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel. Then, a monomer mixture for forming an elastic body consisting of 90 parts of β-farnesene (FA), 10 parts of styrene (St), and 5 parts of 1,3-butylene glycol dimethacrylate was added to the polymerization vessel all at once. 0.06 parts of paramenthane hydroperoxide was added to the polymerization vessel as a polymerization initiator immediately after the addition of the mixed components all at once (0 hours after the addition all at once) and 10 times every hour thereafter (total of 11 times, total amount of 0.66 parts). A latex of elastic body (FR-1) was obtained in which the polymerization conversion rate of the components constituting the elastic body was 99%. The volume average particle size of the elastic body (FR-1) was 24 nm, and the solid content of the latex of the elastic body (FR-1) was 34%.

[0161] <Production of the graft part> 206 parts of the latex of the elastic body (FR-1) (70 parts of the elastic body) and water were charged into a polymerization vessel equipped with a stirrer so that the total amount of the water contained in the latex of the elastic body (FR-1) was 300 parts, and after nitrogen replacement, the temperature was raised to 60° C. Next, 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.2 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel.

[0162] Then, as the first stage of graft polymerization, 15 parts of methyl methacrylate (MMA) and 0.08 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 75 minutes to carry out polymerization, and then further polymerized for 30 minutes. As the second stage of graft polymerization, a mixture of 15 parts of styrene (St) and 0.16 parts of t-butyl hydroperoxide as a polymerization initiator was continuously added over 75 minutes to carry out polymerization, and 10 minutes after the completion of the addition, 0.075 parts of sodium formaldehyde sulfoxylate was added, and 10 minutes later, 0.06 parts of t-butyl hydroperoxide was added, and post-polymerization was carried out for another 80 minutes. A latex of polymer fine particles (FG-1) was obtained, in which the polymerization conversion rate of the components constituting the graft portion was 90%. The volume average particle diameter of the polymer fine particles (FG-1) was 24 nm, and the solid content concentration of the latex of the polymer fine particles (FG-1) was 24.5%.

[0163] <Production of powders and granules> To the latex of the obtained polymer microparticles (FG-1), 2.0 parts of an emulsified antioxidant (BASF hindered phenol-based antioxidant) was added, and 2.0 parts of calcium chloride was added at room temperature or lower (5°C to 10°C). This resulted in the polymer microparticles being solidified while adjusting the amount of water so that the slurry concentration became 10%. The obtained slurry was subjected to a heat treatment at a temperature of 80°C to 90°C, and then the slurry was cooled to room temperature and dehydrated. It was then subjected to a drying treatment at 50°C to obtain powdered polymer microparticles, i.e., powdered granules. The obtained powdered granules were mixed with polyvinyl chloride according to the above-mentioned method, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0164] Example 2 <Manufacturing of Elastic Body> The same method as in Example 1 was carried out, except that the monomer components added all at once were changed to a monomer mixture for forming an elastomer, consisting of 100 parts of β-farnesene (FA) and 5 parts of 1,3-butylene glycol dimethacrylate. A latex of an elastomer (FR-2) was obtained, in which the polymerization conversion rate of the components constituting the elastomer was 100%. The volume average particle diameter of the elastomer (FR-2) was 25 nm, and the solid content concentration of the latex of the elastomer (FR-2) was 34%. <Production of graft parts, production of powder and granules> For the latex of the elastic body (FR-2) in an amount of 70 parts solid content, 15 parts of styrene (St) and 0.16 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 75 minutes as the first stage of graft polymerization, and polymerization was performed for 30 minutes. Then, as the second stage of graft polymerization, 15 parts of methyl methacrylate (MMA) and 0.08 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 75 minutes, except that polymerization was performed in the same manner as in Example 1. A latex of polymer fine particles (FG-2) was obtained in which the polymerization conversion rate of the components constituting the graft portion was 99%. The volume average particle diameter of the polymer fine particles (FG-2) was 26 nm, and the solid content concentration of the latex of the polymer fine particles (FG-2) was 25%. Powdered polymer fine particles, i.e., powdered granules, were obtained by the same method as in Example 1, and various physical properties were evaluated. The results are shown in Table 1.

[0165] Example 3 <Manufacturing of Elastic Body> Except for changing the amount of 1,3-butylene glycol dimethacrylate from 5 parts to 10 parts, a latex of an elastic body (FR-3) having a polymerization conversion rate of 100% of the components constituting the elastic body was produced by the same method as in Example 2. The volume average particle diameter of the elastic body (FR-3) was 28 nm, and the solid content concentration of the latex of the elastic body (FR-3) was 34%.

[0166] <Production of graft parts, production of powder and granules> Graft polymerization was carried out on the elastomer (FR-3) in the same manner as in Example 2. A latex of polymer microparticles (FG-3) was obtained in which the polymerization conversion rate of the components constituting the graft moiety was 99%. The volume average particle diameter of the polymer microparticles (FG-3) was 28 nm, and the solid content concentration of the latex of the polymer microparticles (FG-3) was 25%. Powdered polymer microparticles were obtained in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0167] Example 4 <Manufacturing of Elastic Body> The latex of the elastic body (FR-2) obtained in Example 2 was used.

[0168] <Production of graft parts, production of powder and granules> For the latex of the elastic body (FR-2) in an amount to give a solid content of 60 parts, 25 parts of styrene (St) and 0.27 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 125 minutes as the first stage of graft polymerization, and polymerization was performed for 30 minutes. Then, as the second stage of graft polymerization, 15 parts of methyl methacrylate (MMA) and 0.08 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 75 minutes, except that polymerization was performed. A latex of polymer fine particles (FG-4) was obtained in which the polymerization conversion rate of the components constituting the graft portion was 90%. The volume average particle diameter of the polymer fine particles (FG-4) was 30 nm, and the solid content concentration of the latex of the polymer fine particles (FG-4) was 24.5%. Powdered polymer fine particles, i.e., powdered granules, were obtained by the same method as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0169] Comparative Example 1 <Manufacturing of Elastic Body> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer, and the temperature was raised to 40°C. Next, 0.0048 parts of ferrous sulfate (FeSO4·7H2O), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added to the pressure-resistant polymerization vessel equipped with a stirrer, and degassed. Then, 1.8 parts of sodium oleate, 100 parts of 1,3-butadiene, and 0.06 parts of paramenthane hydroperoxide were added to the pressure-resistant polymerization vessel equipped with a stirrer to start polymerization. Immediately after 2 hours had elapsed from the start of polymerization, 0.02 parts of sodium formaldehyde sulfoxylate were added, and immediately after 3 hours had elapsed from the start of polymerization, 0.02 parts of paramenthane hydroperoxide were added. Immediately after 10 hours had elapsed from the start of polymerization, 0.2 parts of sodium oleate were added, and the temperature was raised to 50°C. Immediately after 12 hours from the start of polymerization, 0.02 parts of paramenthane hydroperoxide was added, and immediately after 13 hours from the start of polymerization, 0.03 parts of paramenthane hydroperoxide was added, and polymerization was continued. A latex of elastomer (BR-1) was obtained, in which the polymerization conversion rate of the components constituting the elastomer was 95%. The volume average particle diameter of elastomer (BR-1) was 83 nm, and the solid content concentration of the latex of elastomer (BR-1) was 36%.

[0170] <Production of graft parts, production of powder and granules> 194 parts of the latex of the elastic body (BR-1) (solid content 70 parts) and water were charged into a polymerization vessel equipped with a stirrer so that the total amount of the water contained in the latex of the elastic body (BR-1) was 250 parts, and after nitrogen replacement, the temperature was raised to 60°C. 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.06 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel equipped with a stirrer. Then, as the first stage of graft polymerization, 20 parts of methyl methacrylate (MMA), 5 parts of butyl acrylate (BA), 5 parts of styrene (St), and 0.108 parts of t-butyl hydroperoxide as a polymerization initiator were continuously added over 150 minutes to polymerize. 10 minutes after the end of the addition, 0.075 parts of sodium formaldehyde sulfoxylate was added, and 10 minutes after that, 0.06 parts of t-butyl hydroperoxide was added, and polymerization was continued for another 80 minutes. This resulted in a latex of polymer fine particles (BG-1) with a polymerization conversion rate of 99% of the components constituting the graft moiety. The volume average particle diameter of the polymer fine particles (BG-1) was 85 nm, and the solid content concentration of the latex of the polymer fine particles (BG-1) was 28%. Powdered polymer fine particles, i.e., granular material, were obtained by the same method as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0171] Comparative Example 2 <Production of graft parts, production of powder and granules> 194 parts (solid content 70 parts) of the latex of the elastic body (BR-1) obtained by the same method as in Comparative Example 1 and water were charged into a polymerization vessel equipped with a stirrer so that the total amount of the water contained in the latex of the elastic body (BR-1) was 250 parts, and after nitrogen replacement, the temperature was raised to 60°C. 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.2 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel equipped with a stirrer. Then, 15 parts of styrene (St) were polymerized in the first stage and 15 parts of methyl methacrylate (MMA) were polymerized in the second stage by the same method as in Example 2. As a result, a latex of polymer fine particles (BG-2) with a polymerization conversion rate of 99% of the graft portion was obtained. The volume average particle diameter of the polymer fine particles (BG-2) was 86 nm, and the solid content concentration of the latex of the polymer fine particles (BG-2) was 28%. Powdered polymer fine particles, i.e., powdered granules, were obtained in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0172] Comparative Example 3 <Manufacturing of Elastic Body> An elastomer was produced in the same manner as in Comparative Example 1, except that 100 parts of 1,3-butadiene was replaced with 76 parts of 1,3-butadiene and 24 parts of styrene (St). This resulted in the production of a latex of elastomer (SBR-1) with a polymerization conversion rate of 95% of the components constituting the elastomer. The volume average particle size of the elastomer (SBR-1) was 67 nm, and the solid content of the latex of the elastomer (SBR-1) was 36%.

[0173] <Production of graft parts, production of powder and granules> 167 parts of the latex of the elastic body (SBR-1) (60 parts of solids) and water were charged into a polymerization vessel equipped with a stirrer so that the total amount of the water contained in the latex of the elastic body (SBR-1) was 250 parts. After nitrogen replacement, the temperature was raised to 60°C by the same method as in Comparative Example 2, ferrous sulfate, EDTA·2Na, and sodium formaldehyde sulfoxylate were added, and 15 parts of methyl methacrylate (MMA) and 12 parts of butyl acrylate (BA) were polymerized as the first stage of graft polymerization, and 13 parts of styrene (St) were polymerized as the second stage of graft polymerization. As a result, a latex of polymer fine particles (BG-3) was obtained in which the polymerization conversion rate of the components constituting the graft portion was 100%. The volume average particle diameter of the polymer fine particles (BG-3) was 70 nm, and the solid content concentration of the latex of the polymer fine particles (BG-3) was 28%. Powdered polymer fine particles, i.e., powdered granules, were obtained in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0174] Comparative Example 4 <Manufacturing of Elastic Body> A monomer mixture for forming an elastomer, consisting of 100 parts of β-farnesene (FA) and 5 parts of 1,3-butylene glycol dimethacrylate, was polymerized in the same manner as in Example 2. The polymerization conversion rate of the components constituting the elastomer was 100%, the volume average particle size was 25 nm, and the solid concentration of the latex was 34%. An enlarger called aggregating latex was added to this elastomer, and the pH was adjusted to obtain an elastomer (FR-4) with a volume average particle size of 300 nm.

[0175] <Production of graft parts, production of powder and granules> Graft polymerization was carried out in the same manner as in Example 2, except that the elastomer (FR-2) in Example 2 was changed to the elastomer (FR-4), and a latex of polymer particles (FG-5) was obtained in which the polymerization conversion rate of the components constituting the graft moiety was 99%. The volume average particle diameter of the polymer particles (FG-5) was 313 nm, and the solid content concentration of the latex of the polymer fine particles (FG-5) was 25%. Powdered polymer fine particles, i.e., granular material, were obtained in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Table 1.

[0176] Comparative Example 5 <Manufacturing of Elastic Body> An elastomer was produced in the same manner as in Comparative Example 1, except that 100 parts of 1,3-butadiene were replaced with 29 parts of 1,3-butadiene, 42 parts of β-farnesene (FA), and 29 parts of styrene (St). This resulted in the production of a latex of elastomer (FR-5) with a polymerization conversion rate of 95% of the components constituting the elastomer. The volume average particle size of the elastomer (FR-5) was 50 nm, and the solid content of the latex of the elastomer (FR-5) was 36%.

[0177] <Production of graft parts, production of powder and granules> In the same manner as in Comparative Example 1, 194 parts (70 parts solids) of the latex of the elastic body (FR-5) and water were charged into a pressure-resistant polymerization vessel equipped with a stirrer so that the total amount of the water contained in the latex of the elastic body (FR-5) was 250 parts. The temperature was raised to 60°C, and 0.0056 parts of ferrous sulfate (FeSO4·7H2O), 0.0094 parts of EDTA·2Na, and 0.06 parts of sodium formaldehyde sulfoxylate were added and degassed. Then, 15 parts of β-farnesene and 15 parts of 1,3-butadiene were charged in one go as components of the graft portion. Then, 0.06 parts of paramenthane hydroperoxide were added to start polymerization, and then paramenthane hydroperoxide was appropriately added to complete the polymerization. As a result, a latex of polymer fine particles (FG-6) was obtained in which the polymerization conversion rate of the components constituting the graft portion was 100%. The volume average particle diameter of the polymer microparticles (FG-6) was 57 nm, and the solid content of the latex of the polymer microparticles (FG-6) was 28%. Powdered polymer microparticles, i.e., powder particles, were obtained in the same manner as in Example 1, and various physical properties were evaluated. The results are shown in Tables 1 and 2.

[0178] [Table 1]

[0179] [Table 2]

[0180] <Summary> In one embodiment of the present invention, the polymer microparticles contain an elastomer that contains farnesene units and has a volume average particle diameter of less than 50 nm, making it possible to provide a resin composition with excellent flowability and a molded article with excellent impact resistance. [Industrial Applicability]

[0181] The polymer microparticles according to one embodiment of the present invention can be preferably used in adhesives, coating materials, molded articles, films, etc. by being blended with a matrix resin. As application fields, the polymer microparticles can be preferably used in stationery applications, food packaging applications, electrical and electronic applications, building materials applications, vehicle applications, etc.

Claims

1. an elastomer containing farnesene units and having a volume average particle size of less than 50 nm; and a graft portion graft-bonded to the elastomer.

2. The elastic body is 2. The polymer microparticle according to claim 1, comprising one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.

3. The elastic body contains, based on 100% by weight of the constituent units, Contains 5.0% to 99.9% by weight of the farnesene unit; and 2. The polymer microparticle according to claim 1, comprising 0.1% by weight to 95.0% by weight in total of one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units.

4. The elastic body contains, based on 100% by weight of the constituent units, The composition contains 0% by weight to 95.0% by weight of diene units other than the farnesene units, The vinyl unit is contained in an amount of 0% by weight to 50.0% by weight, and The polymer microparticles according to claim 3, comprising 0 to 20.0% by weight of said polyfunctional units.

5. The elastic body is 2. The polymer microparticles according to claim 1, comprising styrene units and / or alkyl (meth)acrylate units.

6. The elastomer contains styrene units, 2. The polymer microparticle according to claim 1, wherein the content of said styrene unit is 20.0% by weight or less in 100% by weight of the constituent units of said elastic body.

7. The polymer microparticles according to claim 1 , wherein the graft moiety comprises a styrene unit.

8. The polymer microparticles according to claim 7 , wherein the elastomer comprises a styrene unit.

9. The polymer microparticles according to claim 7 , wherein the elastomer does not contain a styrene unit.

10. A resin composition comprising the polymer fine particles according to any one of claims 1 to 9 and a matrix resin.

11. The resin composition according to claim 10, wherein the matrix resin is polyvinyl chloride.

12. A molded article obtained by molding the resin composition according to claim 10.

Citation Information

Patent Citations

  • Coated polymer particles, resin modifier, rubber composition, and tire

    WO2017038724A1